PEMETAAN GAGASAN PADA TEKS LAPORAN DAN ANALISIS KESALAHAN BERBAHASA SMP KELAS 7 - Markhamah, Markhamah; Darmasari, Nindi Muliasa (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study examines the analysis of language errors in report texts for 7th grade junior high school (SMP) students. The background of this research is what forms of language errors often occur in student report texts and why students still experience language errors when writing scientific papers such as reports. The purpose of this study was to examine the analysis of students' academic writing errors. own terminology. The data collection technique of this research is direct observation and analysis of the report text obtained. the results of the discussion found several language errors in the fields of phonology, morphology, semantics, syntax. language errors that occur in the report text of grade 7 junior high school students are caused by the low writing and reading skills of students. As well as the low mastery of student vocabulary so that there are several forms of writing that are wrong and not in accordance with the Big Indonesian Dictionary (KBBI). Conclusions can be written in paragraph form. The level of accuracy and neatness of students in writing report texts is also very influential on the final results of their writing later.